Is political risk a driver of SMEs leverage? - Georgios Savvakis; Dimitris Kenourgios; Theofanis Papageorgiou (Applied Economics Letters, 2021)
This paper employs econometric techniques in order to examine the role of political risk on the capital structure decisions of European listed SMEs, during a period which fully captures the Euro zone debt crisis and aspects of political risk due to the recession and its over-indebtedness. We find that political risk decreases significantly SMEs leverage via different and significant transmission channels. Very small (micro) enterprises are decreasing more significantly their leverage at times of political risk. The strength of the creditor’s rights act as a proxy for the possible effects of the political risk. Political risk combined with corruption has a positive effect on firm leverage.